2017
DOI: 10.7860/jcdr/2017/27396.10405
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic Hyalinizing Angiectatic Tumour: A Rare Case Report and Discussion of Differential Diagnosis

Abstract: A 50-year-old man presented with a solitary, slow growing mass in the left calf region since two years. The patient gave history of rapid increase in size of the swelling since two months following thorn injury. Magnetic Resonance Imaging (MRI) revealed a large well defined lobulating heterogenous soft tissue malignant neoplasm arising from posteromedial aspect of gastrocnemius muscle extending into subcutaneous plane. Fine Needle Aspiration Cytology (FNAC) of the swelling revealed a low cellular smear with bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…1,60 PHAT shares morphological characteristics with SFT and giant cell angiofibroma. 1,19,34,59 Nuclear atypia found in PHAT are more prominent than those seen in SFT, and the presence of multinucleated giant cells is seen only in PHAT. 1,19,34,59 Prominent clusters of thin-walled ectatic vessels surrounded by perivascular hyaline material are characteristic in PHAT, but may also be present in solitary fibrous tumors and giant cell angiofibromas, and may correspond to secondary changes due to circulation disorders often seen in tumors of slow growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,60 PHAT shares morphological characteristics with SFT and giant cell angiofibroma. 1,19,34,59 Nuclear atypia found in PHAT are more prominent than those seen in SFT, and the presence of multinucleated giant cells is seen only in PHAT. 1,19,34,59 Prominent clusters of thin-walled ectatic vessels surrounded by perivascular hyaline material are characteristic in PHAT, but may also be present in solitary fibrous tumors and giant cell angiofibromas, and may correspond to secondary changes due to circulation disorders often seen in tumors of slow growth.…”
Section: Discussionmentioning
confidence: 99%
“…61 The main differential diagnoses found in the searches are schwannoma, pleomorphic sarcomas (formerly called malignant fibrous histiocytoma), s o l i t a r y f i b r o u s t u m o r ( S F T ) a n d g i a n t c e l l angiofibroma. 1,18,19,34,62,63 Tumor cells resemble those of pleomorphic sarcomas, but differ from them by the presence of prominent intranuclear cytoplasmic pseudoinclusions, the scarcity of mitotic figures, and the frequent presence of CD34 expression. 1,59 These tumors also share several characteristics with schwannomas, such as their hyalinized vessel wall, intranuclear cytoplasmic inclusions, very low mitotic activity, and the presence of mast cells; however, they are differentiated by the frequent presence of infiltrating margins and the absence of S-100 protein labeling.…”
Section: Discussionmentioning
confidence: 99%
“…The average dimensions were around 5.3 cm, with an exceptional case of 26.3 cm in male breast reported by Lee et al in 2005 [ 16 ]. Interestingly, Wei et al [ 26 ] and Chalmeti et al [ 35 ] reported two cases of PHAT respectively at the level of the renal hilum and within the kidney itself, emphasizing the potential problem of confusing this entity with other neoplasms of kidney. Our data completely agrees with Rush et al [ 41 ], who in a recent article in 2018 conducted a detailed review of the literature more focused on the surgical-oncological implications related to PHAT.…”
Section: Discussionmentioning
confidence: 99%
“…In most of cases it has a lobulated appearance, with a gray to light brown cut surface. It is never encapsulated, and many of these lesions have diffusely infiltrative edges, although well-defined margins [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Sometimes, PHAT can have a prominent cystic component [ 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation